Aplikasi SmartRoom Berbasis Blynk untuk Mengurangi Pemakaian Tenaga Listrik - Richard Prayogo Gozal; Alexander Setiawan; Handry Khoswanto (Jurnal Infra, 2020)
This study aims to create a Blynk-based application as a controller for SmartRoom to reduce unnecessary electricity usage. As for the background of this writing because today almost all activities that humans do everyday are related to electricity usage. But there are also many people who use electricity powerfully. This excessive use of electricity can cause energy waste and increase electricity costs. With increasing electricity usage, savings can be made by turning off lights or electrical appliances that are not used through the help of the Internet of Things through Blynk-based applications.The making of this application is made using the interaction between the microcontoler WeMos D1 R2 which is connected with sensors and modules to detect data to be processed for SmartRoom. For applications using Blynk which is connected to the system and used to make it easier for users to control devices that are connected remotely.The results showed that in a trial period of 1 week between normal conditions and the SmartRoom system resulted in a power savings of 28% and could be realized with a reliability level of 100%.